Scaffold microarchitecture regulates angiogenesis and the regeneration of large bone defects. (1st October 2022) - Eichholz, Kian F; Freeman, Fiona E; Pitacco, Pierluca; Nulty, Jessica; Ahern, Daniel; Burdis, Ross; Browe, David C; Garcia, Orquidea; Hoey, David A; Kelly, Daniel J
Abstract: Emerging 3D printing technologies can provide exquisite control over the external shape and internal architecture of scaffolds and tissue engineering (TE) constructs, enabling systematic studies to explore how geometric design features influence the regenerative process. Here we used fused deposition modelling (FDM) and melt electrowriting (MEW) to investigate how scaffold microarchitecture influences the healing of large bone defects. FDM was used to fabricate scaffolds with relatively large fibre diameters and low porosities, while MEW was used to fabricate scaffolds with smaller fibre diameters and higher porosities, with both scaffolds being designed to have comparable surface areas. Scaffold microarchitecture significantly influenced the healing response following implantation into critically sized femoral defects in rats, with the FDM scaffolds supporting the formation of larger bone spicules through its pores, while the MEW scaffolds supported the formation of a more round bone front during healing. After 12 weeks in vivo, both MEW and FDM scaffolds supported significantly higher levels of defect vascularisation compared to empty controls, while the MEW scaffolds supported higher levels of new bone formation. Somewhat surprisingly, this superior healing in the MEW group did not correlate with higher levels of angiogenesis, with the FDM scaffold supporting greater total vessel formation and the formation of larger vessels, while the MEW scaffold promoted the formation of a dense microvasculature with minimal evidence of larger vessels infiltrating the defect region. To conclude, the small fibre diameter, high porosity and high specific surface area of the MEW scaffold proved beneficial for osteogenesis and bone regeneration, demonstrating that changes in scaffold architecture enabled by this additive manufacturing technique can dramatically modulate angiogenesis and tissue regeneration without the need for complex exogenous growth factors. These results provide a valuable insight into the importance of 3D printed scaffold architecture when developing new bone TE strategies.